2009
DOI: 10.2987/09-0006.1
|View full text |Cite
|
Sign up to set email alerts
|

Repellency of Essential Oil of Piper aduncum Against Aedes albopictus in the Laboratory

Abstract: The repellent activity of Piper aduncum essential oil against Aedes albopictus was investigated under laboratory conditions with human volunteers. The lowest median effective dose (ED50) value was 1.5 microg/cm2 at 60 sec of exposure when compared to 90 sec (2.1 microg/cm2) and 120 sec (1.8 microg/cm2) of exposure. At 0.4 g, the essential oil gave a high protection (95.2%) against Ae. albopictus bites or landing at 2 h postapplication. The percentage of protection was reduced to 83.3% after 4 h, 64.5% after 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…aegypti has decreased from high prevalence in 1907 to relict populations in remote valleys today in Mayotte. It was [16] reported that in certain human dwellings/habitats, Ae. albopictus were ovipositing inside the premises and was predominant in population compared to Ae.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti has decreased from high prevalence in 1907 to relict populations in remote valleys today in Mayotte. It was [16] reported that in certain human dwellings/habitats, Ae. albopictus were ovipositing inside the premises and was predominant in population compared to Ae.…”
Section: Discussionmentioning
confidence: 99%
“…These studies can be broken down into a series of categories: 1) standard ethnobotanical studies and evaluations of plants that are traditionally used to repel mosquitoes [17,67-70]; 2) standard dose response [33] laboratory evaluations of solvent extractions of plants without DEET positive controls [71]; 3) standard dose response [33] laboratory evaluations of solvent or extractions or essential oils of plants with DEET positive controls [72] coupled with GC-MS (coupled gas chromatography-mass spectrometry) [73]; 4) laboratory evaluations using time to first bite method [74] comparing the plant repellents to DEET [75] and in addition several of those studies also analysed the constituents of the oil through GC-MS [76,77]. In addition there were a large number of studies that did not use the accepted standard methodology [78] (Table 3), and should be interpreted with caution.…”
Section: Considerations For Repellent Testing Methodologymentioning
confidence: 99%
“…For the effect against Ae. albopictus, the lowest median effective dose (ED 50 ) value was 2.1 ug/cm2 at 90 seconds of exposure (Misni et al 2009). Furthermore, field evaluation by ultra-low-volume (ULV) spray against dengue vector using Litsea elliptica extracts and bifenthrin indicated low larvacidal effect but the extract caused 96.5 -97.6% mortality among Ae.…”
Section: Introductionmentioning
confidence: 98%